Oral vs. Intravenous Antibiotics for the Treatment of Acute Bacterial Osteomyelitis in the Veteran Population. (4th October 2017) - Turnbull, Caitlin; Young, Lisa; Lowery, Sheryl
Abstract: Background: The optimal route for administration of antibiotics in the treatment of acute bacterial osteomyelitis (ABOM) has not been clearly defined. Based on pharmacokinetic data and expert opinion, intravenous (IV) antibiotics are considered the standard of care. Studies demonstrate reasonable oral (PO) absorption and bone penetration of certain antibiotics, supporting the potential efficacy of their use in the treatment of ABOM. The purpose of this study was to determine whether a difference exists in treatment outcomes in Veterans with ABOM treated with PO vs. IV antibiotics. Methods: This is a retrospective, electronic chart review of patients diagnosed with ABOM between October 1, 2008, and September 30, 2013. Subjects were evaluated and placed into two groups: (1) IV antibiotics for at least 4 weeks or (2) PO antibiotics for at least 4 weeks. The primary endpoint was treatment failure within one year of diagnosis. Treatment failure was defined as recurrence of infection, amputation of the infected bone, or if they were lost to follow-up. Results: In total, 83 patients, accounting for 89 episodes of ABOM were included in this study; 41 in the IV group and 48 in the PO group. Treatment failure occurred in 14 patients in the IV group (34.15%) and 17 patients in the PO group (35.42%), P = 0.90. Subgroup analysis of subjects with diabetes mellitus, peripheral vascular disease, body mass index ≥ 30 kg/m 2, and those ≥ 65 years also found no difference between groups. After at least 4 weeks of antibiotic therapy, 10 patients in the IV group and five patients in the PO group had an amputation of the infected bone, P = 0.14. Mean length of hospital stay was significantly longer in the IV group at 8.55 days as compared with the PO group at 2.23 days, P  < 0.0001. Conclusion: Treatment of ABOM with PO antibiotics may serve as a reasonable alternative to IV antibiotics, showing similar efficacy and reduced hospital stay. Disclosures: All authors: No reported disclosures.